Behavioural measurement of postoperative pain after oral surgery - P. Coulthard, B. J. Pleuvry,* M. Dobson, M. Price (Blackwell Synergy, 2000)
Clinicians have a considerable amount of responsibility and power in relation to what is given to relieve postoperative pain. The type and amount of analgesia prescribed relies on critical judgement in terms of what is required.1 Among other factors this judgement is likely to be based on the patient’s behaviour and analgesia may be withheld if the patient seems to have no pain.